Detection of human disease conditions by single-cell morpho-rheological phenotyping of blood - Toepfner, Nicole; Herold, Christoph; Otto, Oliver; Rosendahl, Philipp; Jacobi, Angela; Kraeter, Martin; Staechele, Julia; Menschner, Leonhard; Herbig, Maik; Ciuffreda, Laura; Ford-Cartwright, Lisaran; Grzybek, Michal; et al. (eLife, 2018)
Blood is arguably the most important bodily fluid and its analysis provides crucial health status information. A first routine measure to narrow down diagnosis in clinical practice is the differential blood count, determining the frequency of all major blood cells. What is lacking to advance initial blood diagnostics is an unbiased and quick functional assessment of blood that can narrow down the diagnosis and generate specific hypotheses. To address this need, we introduce the continuous, cell-by-cell morpho-rheological (MORE) analysis of diluted whole blood, without labeling, enrichment or separation, at rates of 1000 cells/sec. In a drop of blood we can identify all major blood cells and characterize their pathological changes in several disease conditions in vitro and in patient samples. This approach takes previous results of mechanical studies on specifically isolated blood cells to the level of application directly in blood and adds a functional dimension to conventional blood analysis.
CRIS-Team Scopus Importer:2022-08-05